2020
DOI: 10.21037/tau.2019.12.31
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted partial nephrectomy of initial cases using a 3D square-block type kidney model

Abstract: Background: It is extremely important to understand the local anatomy prior to performing appropriate and efficient robot-assisted partial nephrectomies (RAPNs).Methods: We developed a personalized three-dimensional printed kidney model of square-block type to enhance our knowledge and understanding on the underlying anatomy during RAPN, and we consequently applied this model to six initial cases of RAPN.Results: The mean warm ischemic time was 18 minutes and the mean estimated blood loss was 59 mL.Only one pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…According to a previous article (7), each final printed model was actual size and had a square-block structure so that the inside could be seen (see Figure 1 for representative images). In the model, arteriovenous arterioles could be reproduced up to the tertiary branches and the branching of the quadratic branches.…”
Section: Three-dimensional Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a previous article (7), each final printed model was actual size and had a square-block structure so that the inside could be seen (see Figure 1 for representative images). In the model, arteriovenous arterioles could be reproduced up to the tertiary branches and the branching of the quadratic branches.…”
Section: Three-dimensional Modelmentioning
confidence: 99%
“…In a report using 3D-printed soft-tissue physical models as preoperative simulation in 7 cases, it was also reported that bleeding was reduced (3). In this study, we describe the creation of a novel, simple, and inexpensive 3D-printed model of the kidney that contains the minimal anatomical information required for RAPN (e.g., the tumor, artery, vein, and urinary tract) (7). We aimed to determine the usefulness of this model during initial experience with RAPN and whether its use would contribute to the achievement of TRIFECTA, defined as the absence of perioperative complications, positive surgical margins, and a WIT of <25 min.…”
Section: Introductionmentioning
confidence: 99%
“…We used a UP plus2 (Beijing Tiertime Technology Co., Ltd., Beijing, China) 3D printer, which is a Fused Deposition Modeling type of 3D printer that utilizes acrylonitrile butadiene styrene resin to make the 3D kidney models as described in previous studies [8,9]. The Standard Triangulated Language (STL) data from contrast-enhanced CT scans or plain MRI were prepared by a radiology technologist.…”
Section: Development Of the 3d Modelmentioning
confidence: 99%
“…The procedure initially evolved from open PN (OPN) to laparoscopic PN (LPN), while in recent years, robot-assisted PN (RAPN) has become more common. Progress towards less invasive and safer surgery has been steady, supported by technological development and ingenuity such as in the use of 3D models (3)(4)(5). One of the most stressful and life-threatening complications for patients who undergo PN is renal artery pseudoaneurysm (RAP) (6).…”
Section: Introductionmentioning
confidence: 99%
“…R.E.N.A.L. nephrometry score, median[IQR, range] 7[3,[4][5][6][7][8][9][10] R.E.N.A.L. nephrometry score, low[4][5][6]/moderate[7][8][9]/high[10][11][12]IQR, interquartile range; BMI, body mass index; ASA-PS, American Society of Anesthesiologists physical status; eGFR, estimated glomerular filtration rate; R.E.N.A.L., radius (tumor size as maximal diameter), exophytic/endophytic properties of tumor, nearness of tumor deepest portion to collecting system or sinus, anterior/posterior descriptor and location relative to polar line; RCC, renal cell carcinoma.Transl Androl Urol 2021 | https://dx.doi.org/10.21037/tau-21-384 © Translational Andrology and Urology.…”
mentioning
confidence: 99%